ChemInform Abstract: New Preparation of TMPZnCl·LiCl by Zn Insertion into TMPCI. Application to the Functionalization of Dibromodiazines. Issue 26 (6th June 2013) - Unsinn, Andreas; Ford, Mark J.; Knochel, Paul
Abstract The reported procedure involves cheap and safe reagents under mild conditions.